2013
DOI: 10.3168/jds.2013-7015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus kefiranofaciens M1 isolated from kefir grains on enterohemorrhagic Escherichia coli infection using mouse and intestinal cell models

Abstract: A potential probiotic strain, Lactobacillus kefiranofaciens M1, was previously isolated from kefir grains, which are used to manufacture the traditional fermented drink kefir. The aim of this study was to investigate the effects of Lb. kefiranofaciens M1 on enterohemorrhagic Escherichia coli (EHEC) infection, using mice and intestinal cell models. BALB/c mice were daily administrated with either phosphate buffered saline or Lb. kefiranofaciens M1 at 2×10(8) cfu/mouse per day intragastrically for 7 d. Intragast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…The presence of these genes suggests that the L. kefiranofaciens strains present in these kefirs have the potential to survive gastric transit, colonize the gut, and inhibit the growth of pathogens. Indeed, previous studies using mice have shown that L. kefiranofaciens protects against enterohemorrhagic Escherichia coli infection (44). Further analysis of shotgun metagenomic data from cheese and kimchi indicated that similar genes are present in other fermented foods.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these genes suggests that the L. kefiranofaciens strains present in these kefirs have the potential to survive gastric transit, colonize the gut, and inhibit the growth of pathogens. Indeed, previous studies using mice have shown that L. kefiranofaciens protects against enterohemorrhagic Escherichia coli infection (44). Further analysis of shotgun metagenomic data from cheese and kimchi indicated that similar genes are present in other fermented foods.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo study where BALB/c mice were intragastrically challenged with E. coli O157:H7, mice receiving L . kefiranofaciens M1 prior to E. coli challenge showed reduced symptoms of infection, including intestinal and renal damage, bacterial translocation, and Shiga toxin penetration as well as increased EHEC-specific mucosal IgA responses ( Chen et al, 2013 )…”
Section: Effects On the Host Gut And Gut Microbiomementioning
confidence: 99%
“…Previous studies have reported that administering probiotics to humans and animal models is beneficial in treating and preventing intestinal infections as well as reducing mucosal inflammation Chen, Hsiao, Hong, Dai, & Chen, 2012;Chen, Lee, Hong, Hsieh, & Chen, 2013). The ability of deviating tissue cytokine secretions from a proinflammatory to an antiinflammatory profile has been specifically described (Hong, Chen, & Chen, 2010;Shida, Kiyoshima-Shibata, Nagaoka, Watanabe, & Nanno, 2006;Shida et al, 2002).…”
Section: Introductionmentioning
confidence: 97%